THE ROLE OF PUBLIC RELATIONS AT THE OFFICE OF RELIGIOUS AFFAIRS IN RAISING PUBLIC AWARENESS OF SUSTAINABLE MARRIAGE (A Case Study At The Office Of Religious Affairs In Percut Sei Tuan Sub-District, Deli Serdang Regency) - Gita Vita Loka; Salman Kanz; Muhammad Darul Fikhry; Elman (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
The low level of public awareness regarding the importance of mental, spiritual, and legal preparedness in building a household presents a challenge to achieving healthy and sustainable marriages. This study aims to analyze the role of public relations at the Office of Religious Affairs (KUA) in Percut Sei Tuan Sub-District in enhancing community awareness of quality marriages. Using a descriptive qualitative approach and a case study method, data were collected through interviews, observations, and documentation. The findings reveal that the public relations division of the KUA plays a strategic role as an educational facilitator, value communicator, and social connector through programs such as premarital counseling, sakinah family guidance, and the utilization of both traditional and digital media. The KUA applies the Public Information and Two-Way Symmetrical models to deliver messages in both informative and dialogic ways. These findings indicate that professionally managed public relations, grounded in local values, can effectively increase public understanding of the importance of legitimate, healthy, and sustainable marriages. The implications suggest that the KUA should strengthen the capacity of its public relations functions and expand the reach of its educational efforts through more adaptive communication innovations.